IGMESH: A convenient irregular-grid-based pre- and post-processing tool for TOUGH2 simulator. (October 2016) - Hu, Litang; Zhang, Keni; Cao, Xiaoyuan; Li, Yi; Guo, Chaobin
Abstract: As a powerful simulator with input files in fixed-format formats, the capabilities of TOUGH2 simulator urge programmers to develop the pre- and post-processing programs. A new program (IGMESH) with Graphical User Interface (GUI) is introduced. The elements for spatial discrezation are classified into domain bound, boundary for refinement, well, fault, drift and free point, which will be discreted into a series of points. The Voronoi tessellation method is employed to generate Voronoi diagrams in the plane and the relation of neighbor points in a polygon is obtained from the geometric relationship of Voronoi diagrams. Three-dimensional mesh is built based on top elevation and thickness of each model layer. IGMESH provides functions for rock type assignment, boundary conditions, interpolation method of elevation and thickness, simulation results conversion and visualization with TECPLOT software. The case studies in the Beishan area demonstrate the applicability of the approach. IGMESH software has shown to be adequate to build quasi-3D unstructured grids from the beginning of numerical model build to the results analysis, and thus will facilitate the application of TOUGH2 simulator. Highlights: A new quick and convenient pre- and post- processing tool for TOUGH2 is introduced. IGMESH closely links TOUGH2 and TECPLOT software from model build to results analysis. An example demonstrates the applicability of IGMESH.